A Two-Factor Hazard Rate Model for Pricing Risky Debt and the Term Structure of Credit Spreads - Madan, Dilip; Unal, Haluk (Journal of Financial and Quantitative Analysis, 2000)
Dilip Madan, Haluk Unal, A Two-Factor Hazard Rate Model for Pricing Risky Debt and the Term Structure of Credit Spreads, The Journal of Financial and Quantitative Analysis, Vol. 35, No. 1 (Mar., 2000), pp. 43-65